TELAAH FENOMENA POLITISASI AGAMA DI INDONESIA LEWAT KONSEP ASGHAR ALI ENGINEER - Ahmad Nurcholish; Muhammad Rizkita (UIN Sunan Kalijaga Yogyakarta, 2021)
The politics of religion in Indonesia has been growing since the Elections of Region Government in 2007. Anomaly is formed through this phenomenon. Instead of being utilized to promote a civilized community, religion is being exploited as a political instrument to manipulate the people. Asghar Ali Engineer's approach to social justice questioned this oddity. The true essence of religion, according to Engineer, is justice. Muslims should try to accomplish social class generalization in order to build a just society. Islam may be perceived not just spiritually, but also socially from this vantage point. Religion is not a strategy for obtaining and retaining power in Indonesian politics. Politics and religion are said to work together to produce a just and successful society. Religion and politics should be able to work together to solve societal issues. As a result, the existing meaning of the politicization of religion must be reconstructed in order for religion's role in politics to be accurate.